Intergenerational relations and child development in England - Tanskanen, Antti O. (Anthropological Review, 2017)
Evolutionary studies have shown that in many traditional populations the beneficial effects of grandparental presence for grandchildren may vary according to the sex and lineage of the grandparents, as well as by the sex of the grandchild. However, few studies have investigated the relevance of these factors in modern developed societies. The present investigation uses the Millennium Cohort Study (n = 4,636 children) to analyse the association between grandparental investment and child development in contemporary England. Grandparental investment is measured by parent-grandparent contact frequencies at the child’s age of 3 and child development by “early learning goals” over the first year of primary school assessed with the Foundation Stage Profile (FSP). Children whose mothers reported contacts with maternal grandparents receive higher FSP scores compared to those with no contact at all. In addition, children whose fathers reported daily contacts with paternal grandfathers have lower FSP scores than other children. The study provides evidence of the relevance of grandparental investment on grandchild development also in developed societies. The results are discussed with reference to the grandmother hypothesis, sex-specific reproductive strategies and sex chromosome hypothesis.